Tobermorite synthesis under hydrothermal conditions - Dlabajová, Lucie; Másilko, Jiří; Solný, Tomáš; Štěpánková, Eva (Elsevier, 2016)
The influence of different hydrothermal conditions and starting materials on a preparation of tobermorite was examined. Tobermorite is a mineral, which, thanks to its composition and properties, is an important phase in aerated concrete and it can be also used as an ion exchanger. Tobermorite crystallizes together with other calcium silicate hydrates from the system CaO–SiO2–H2O during hydrothermal reactions. Paper deals with the key role of starting materials pre-treatment and its influence on the hydrothermal synthesis process. The other important parameters for a synthesis of pure tobermorite as conditions of the reaction, especially the temperature of hydrothermal reaction and curing time were also studied. Phase composition of prepared samples was characterized by XRD and was confirmed by TG-DTA. For overall product characterization, the SEM was used.

The influence of different hydrothermal conditions and starting materials on a preparation of tobermorite was examined. Tobermorite is a mineral, which, thanks to its composition and properties, is an important phase in aerated concrete and it can be also used as an ion exchanger. Tobermorite crystallizes together with other calcium silicate hydrates from the system CaO–SiO2–H2O during hydrothermal reactions. Paper deals with the key role of starting materials pre-treatment and its influence on the hydrothermal synthesis process. The other important parameters for a synthesis of pure tobermorite as conditions of the reaction, especially the temperature of hydrothermal reaction and curing time were also studied. Phase composition of prepared samples was characterized by XRD and was confirmed by TG-DTA. For overall product characterization, the SEM was used.
Tobermorite synthesis under hydrothermal conditions
Keywords: Tobermorite; hydrothermal synthesis; calcium silicate hydrates; XRD.; Tobermorite; hydrothermal synthesis; calcium silicate hydrates; XRD.